2002
DOI: 10.1046/j.1532-5415.2002.50313.x
|View full text |Cite
|
Sign up to set email alerts
|

Looking at the Relationship Between Hemoglobin Concentration and Prevalent Mobility Difficulty in Older Women. Should the Criteria Currently Used to Define Anemia in Older People be Reevaluated?

Abstract: Our findings raise two hypotheses: (1) Hb currently perceived as "mildly-low" and even "low-normal" might have an independent, adverse effect on mobility function, and (2) Hb of 12.0 g/dL might be a suboptimal criterion for defining anemia in older women. Formal testing of these hypotheses might prove relevant for anemia- and mobility disability-related clinical decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
162
4
8

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 254 publications
(191 citation statements)
references
References 33 publications
17
162
4
8
Order By: Relevance
“…Jack and co-workers revealed that 16.6% of the patients had only iron deficiency, 6.4% had folate deficiency only and 5.9% of the patients had B12 deficiency [13]. Hence our study corroborates with the findings of this study, iron deficiency being the most common of the nutrient deficiency anemias.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Jack and co-workers revealed that 16.6% of the patients had only iron deficiency, 6.4% had folate deficiency only and 5.9% of the patients had B12 deficiency [13]. Hence our study corroborates with the findings of this study, iron deficiency being the most common of the nutrient deficiency anemias.…”
Section: Discussionsupporting
confidence: 91%
“…48% of all the cases in our study were anemia of chronic disease with renal insufficiency (45.8%) being the most common underlying cause in anemia of chronic disease which is consistent with various epidemiological studies [13,14].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As a result, as in other observational studies, we do not know which model -the crude model or the fully adjusted model -was the best reflection of the true effect of anemia on functional decline. This may well explain the inconsistent results in other population-based studies of anemia and disability, [23][24][25][26][27] anemia and cognitive impairment or dementia, 3,23,28,29 and anemia and depression 23,24,30 in elderly individuals. These studies all used different levels of control for the confounding effects of comorbidity.…”
Section: Discussionmentioning
confidence: 94%